Sovereign default swap market efficiency and country risk in the eurozone - Yalin Gündüz; Orcun Kaya (Deutsche Bundesbank, 2013)
This paper uses sovereign CDS spread changes and their volatilities as a proxy for the informational efficiency of the sovereign markets and persistency of country risks. Specifically, we apply semi-parametric and parametric methods to the sovereign CDSs of 10 eurozone countries to test the evidence of long memory behavior during the financial crisis. Our analysis reveals that there is no evidence of long memory for the spread changes, which indicates that the price discovery process functions efficiently for sovereign CDS markets even during the crisis. In contrast, both semi-parametric methods and the dual-parametric model imply persistent behavior in the volatility of changes for Greece, Portugal, Ireland, Italy, Spain, and Belgium addressing persistent sovereign uncertainty. We provide evidence of causality from volatility in CDS prices to sovereign risk premiums for these peripheral economies. We furthermore demonstrate the potential spillover effects of spread changes among eurozone countries by estimating dynamic conditional correlations.
Keywords: C22; C58; G01; G15; 330; credit default swaps; long memory; sovereign risk; eurozone economies; FIGARCH; dynamic conditional correlation